Konsep Diri LANSIA di Panti Jompo - Yiyit Yentika (SCHOULID: Indonesian Journal of School Counseling, 2018)
When someone getting old, he/she will get physical changing and physical decreasing which is influencing self-concept decreasing. From the result of introduction study in Tresna Werdha Sabai Nan Aluih Sicincin, the researchers get data as 110 oldsters male and female. Based on the interview to these three elders that has been nursed in this dwelling, one elder says happy although living far away from the family and the brother feels grateful, 2 elders say that they feel sad and yearning of their family. The elders describe their selves that they are old, sick often, and have low self esteem, shy, and feeling inferior. Living in the dwelling is like being thrown away and do not have any interactions anymore.